Aflatoxin contamination of various raw foods arises when a toxin-producing strain, Aspergillus flavus, grows on substrates in areas where suitable environmental conditions are present for the development of the mould. The mould develops on substrates high (Biological Sciences - PJSIR, 2022)
samples were stored in high density polythene bags at -20°Cuntil analysed. The Romer method [7,8] was followed for thequantification [8]. Relevant details of the procedure are gi venin our earlier work [6]. Recovery of the aflatoxin by thestandard addition method ranged between 97-101 %. Eachestimation was performed in triplicate. Aflatoxin referencestandards were obtained from Rijiks institute vwr volkgezondeheit,Bilthoven, Netherland.